Phenotyping of multiple sclerosis lesions according to innate immune cell activation using TSPO-PET - Nylund Marjo; Sucksdorff Marcus; Matilainen Markus; Polvinen Eero; Tuisku Jouni; Airas Laura (Oxford University Press ({OUP}), 2022)
Abstract Chronic active lesions are promotors of neurodegeneration and disease progression in multiple sclerosis. They harbour a dense rim of activated innate immune cells at the lesion edge, which promote lesion growth and thereby induce damage. Conventional MRI is of limited help in identifying the chronic active lesions, so alternative imaging modalities are needed. Objectives were to develop a PET-based automated analysis method for phenotyping of chronic lesions based on lesion-associated innate immune cell activation and to comprehensively evaluate the prevalence of these lesions in the various clinical subtypes of multiple sclerosis, and their association with disability. In this work we use TSPO-PET-imaging for phenotyping chronic multiple sclerosis lesions at large scale. For this, we identified 1510 white matter T1-hypointense lesions from 91 multiple sclerosis patients [67 relapsing-remitting, 24 secondary progressive]. Innate immune cell activation at the lesion rim was measured using PET-imaging and the TSPO-binding radioligand 11C-PK11195. A T1-hypointense lesion was classified as rim-active if the distribution volume ratio of 11C-PK11195-binding was low in the plaque core and considerably higher at the plaque edge. If no significant ligand-binding was observed, the lesion was classified as inactive. Plaques that had considerable ligand-binding both in the core and at the rim were classified as overall-active. Conventional MRI and disability assessment using Expanded Disability Status Scale were performed at the time of PET-imaging. In the secondary progressive cohort, an average of 19% (median, interquartile range 11-26) of T1 lesions were rim-active in each individual patient, compared to 10% (interquartile range 0-20) among relapsing remitting patients (P = 0.009). Secondary progressive patients had a median of 3 (range 0-11) rim-active lesions, vs. 1 (range 0-18) among relapsing remitting patients (P = 0.029). Among those patients who had rim-active lesions (n = 63) the average number of active voxels at the rim was higher among secondary progressive compared to relapsing remitting patients (median 158 versus 74; P = 0.022). The number of active voxels at the rim correlated significantly with Expanded Disability Status Scale (R = 0.43, P <0.001), and the volume of the rim-active lesions similarly correlated with Expanded Disability Status Scale (R = 0.45, P < 0.001). Our study is the first to report in vivo phenotyping of chronic lesions at large scale, based on TSPO-PET. Patients with higher disability displayed a higher proportion of rim-active lesions. The in vivo lesion phenotyping methodology offers a new tool for individual assessment of smouldering (rim-active) lesion burden.